THE PROBLEM BASED LEARNING THEMATIC INTEGRATIVE MODELS TO INCREASE CLASS MANAGEMENT FOR TEACHERS IN ELEMENTARY SCHOOL - Amaliyah, Nurrohmatul (Universitas Pendidikan Indonesia, 2017)
Abstractâ Meaningful learning for a teacher is when it can be understood that the knowledge provided to learners and their changes in the results obtained in the study. As one example of such learning is by using problem based learning thematic integrative. Problem-based learning is a way to acquire the knowledge that combines aspects of cooperative learning and concentrating activities on group work, problem-solving skills and independent learning, as well as discovering the importance of inter-disciplinary knowledge to understand the problem. This learning involves students to solve a problem through the stages of the scientific method so that students can learn the knowledge based on the issues and have the skills to solve problems. While the function of learning with Problem Based Learning method: (1). Learners will increase their problem-solving skills; (2). Its easier to remember; (3). Increased understanding; (4). Increased knowledge relevant to the world of practice; (5). Developing the leadership skills, teamwork, learning skills, and motivate learners. Therefore, this model is very useful for primary school teachers so expect an increase in management learning in the classroom.Keywordsâ Problem Based Learning; Thematic Integrative; Improvement of Classroom Management